Effect of Smoking on Retinal Nerve Fiber Layer Alterations and Dry Eye Disease in Chronic Smokers: Smoking and Retinal Nerve Fiber Layer - Jabbar, Maryam; Ihsan, Khawaja Mohsin; Chaudhary, Muhammad Ajmal; Rashid, Faisal; Khattak, Muhammad Iftikhar; Batool, Amber (Pakistan Journal of Health Sciences, 2024)
Smoking has an impact on the eyes as well because the toxins it contains cause blood flow to be reduced and obstructions to develop in the ocular capillaries, depriving the eye of nutrients that are crucial to its health. Objectives: To evaluate impact of smoking on thickness of the Retinal Nerve Fiber Layer (RNFL) and symptoms of dry eye in chronic smokers. Methods: This study was conducted at Madinah Teaching Hospital, Faisalabad in duration of Sep-Dec, 2023. 30 smokers (60 eyes) who had smoked ≥ 25 cigarettes a day for 10 years were enrolled. For comparison, an equal number of healthy non-smoker were participated as controls. Using a self-structured proforma, data were collected using a non-probability purposive sampling technique. In addition to a thorough history evaluation, a comprehensive slit-lamp examination was performed. schirmer test, Tear Film Breakup Time (TBUT), meibomian gland dysfunction grading and Optical Coherence Tomography (OCT) for RNFL examination were performed. SPSS software was used for analyzing the data. Results: Average age was 49 ± 1.78 years. Each participant was male. Mean schirmer value for smokers was 8 ± 1.71, while the average for non-smokers was 17 ± 1.36 (p=0.02). Similarly, smokers had a tear breakup time of 6 ± 1.89, while non-smokers had a tear breakup time of 15 ± 1.27 (p=0.00). According to the results, smokers' tear film stability is considerably less than that of non-smokers. RNFL thinning was detected in all quadrants in smokers compared to non-smokers (p=0.00). Conclusions: Smoking over an extended period of time is associated with a higher risk of developing dry eye disease and thinning of RNFL.